Effect of Lactation Massage and Oxytocin Massage on Milk Production in Postpartum Women: A Quasi-experimental Study - Agustia, Nency; Camelia, Rini (STIKes Al-Ma'arif Baturaja, 2025)
Exclusive breastfeeding coverage in Indonesia remains below the national target. Low breast milk production in postpartum mothers is one contributing factor. Lactation and oxytocin massage are known to stimulate prolactin and oxytocin hormones to enhance milk production. Objective of this study to determine the effect of a combination of lactation massage and oxytocin massage on breast milk production in postpartum mothers more than two hours after delivery. This quasi-experimental study used a post-test only control group design involving 44 postpartum mothers divided into intervention and control groups. The intervention was performed for three consecutive days. Data were collected using a checklist and observation table. The Mann-Whitney test was used to analyze differences in lactation onset and milk flow. Most mothers in the intervention group experienced a faster lactation onset (95.4%) and smooth milk flow (90.9%), compared to the control group with only 22.7% experiencing fast onset and smooth flow. A significant difference was found between the two groups in both lactation onset (p = 0.015) and milk flow (p = 0.024). The combination of lactation massage and oxytocin massage effectively improves breast milk production in postpartum mothers. This intervention can be adopted as a promotive strategy to support national exclusive breastfeeding targets. Health workers are encouraged to undergo lactation massage training and educate families to implement oxytocin massage at home. Further studies with larger samples are recommended.